THE OFF- LABEL USE OF CARBAMAZEPINE IN INDONESIA - Rahajeng, Bangunawati; Ikawati, Zullies; Murti Andayani, Tri; Dwiprahasto, Iwan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective:. In Indonesia, carbamazepine was approved by The National Agency of Drugs And Foods Controls for the prophylaxis of lithium unresponsive manic-depressive disorders, all types of epilepsy (except for petit mal), and trigeminal neuralgia. This study was conducted to determine the off-label use of carbamazepine in Indonesia. Methods: This research is a nonexperimental descriptive study with a cross-sectional method. Data collection retrospectively by taking all patients that were prescribed carbamazepine in 2014. Data were obtained from four general hospitals in Yogyakarta. The off-label use of carbamazepine was defined a prescribing of carbamazepine outside the indication that approved by The National Agency for Drugs And Foods Controls of Republic of Indonesia (NA-DFC). Results: The use of carbamazepine in 2014 were 704 prescriptions, and on 251 (35.6%) of them were off-label drug use. The off-label use of carbamazepine were 149 prescriptions (59.4%) for neuropathic pain, 83 prescriptions (33.0%) for nociceptive pain, and 19 prescriptions (7.6%) for other indications. Conclusion: The mostly off-label use of carbamazepine in Indonesia was in neuropathic pain with low evidence. Further research to study the efficacy and the risk of off-label use of carbamazepine may be an essential step toward defining the potential for such purpose.